Differential Scanning Calorimeter Profiling for the Determination of Nanoparticle Ethanol Extract of Clove (Syzygium aromaticum L.) Toward Michigan Cancer Foundation-7 Human Breast Cancer Cell Lines - Fadilah, Fadilah (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: This research was conducted to evaluate in vitro assay of nanoparticles ethanol extract of cloves toward Michigan Cancer Foundation-7 human breast cancer cell lines. Materials and Methods: In this research, we have synthesized bud clove extract nanoparticles and analyzed with differential scanning calorimetry. The cytotoxic activity of extract, nanoparticles, and its bioactive component was investigated with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and analyzed by ELISA reader. Results: The in vitro test showed that the IC50 values of the extract and the nanoparticles were 20.13 Î¼g/mL and 7.6 Î¼g/mL, respectively. Conclusion: The ethanol extracts of clove (Syzygium aromaticum L.) could be formulated in nanoparticles form. From cytotoxicity assay, nanoparticle of clove extract showed better cytotoxic activity than the ethanol extract.